Clinical Effectiveness of S2-Alar Iliac Screws in Spinopelvic Fixation in Pediatric Neuromuscular Scoliosis: Systematic Literature Review. Issue 8 (December 2020) - Ravindra, Vijay M.; Mazur, Marcus D.; Brockmeyer, Douglas L.; Kraus, Kristin L.; Ropper, Alexander E.; Hanson, Darrell S.; Dahl, Benny T.
Study Design: Systematic literature review. Objectives: To comprehensively review the S2-alar iliac (S2-AI) screw technique for pelvic fixation in pediatric neuromuscular scoliosis. Methods: Articles identified from the PubMed and EMBASE databases were reviewed for relevance and applicability, and the studies were summarized. Results: Eight articles met the inclusion criteria. A total of 277 pediatric patients underwent spinopelvic fixation using S2-AI fixation for neuromuscular scoliosis; the mean follow-up was 3 years (range = 0.75-6 years). Six articles had level III evidence (5 retrospective cohort studies, 1 observational study), and 2 articles had level IV evidence (case series). Wound complications occurred in 34 (12.2%) patients. Instrumentation complications occurred in 36 patients (13.0%), including lucency around the screw (6.5%), screw fracture (3.6%), disengaging of the set/screw or rod from the tulip head (2.8%), and screw displacement (0.7%). Three patients (1.1%) required reoperation for instrumentation failures. The overall reoperation rate—including 3 hardware replacements and 3 cases of L5-S1 pseudarthrosis—was 2.1%. The mean Cobb angle correction was 51.4°, and the mean pelvic obliquity correction was 14.8°; deformity correction was maintained at 3- and 5-year follow-ups. There were 10 (3.6%) cases of implant prominence/implant-related pain, 1 case of sacroiliac joint pain (resolved with longer screw placement), and no major neurological or vascular complications secondary to S2-AI screw placement. Conclusions: This review suggests that the use of S2-AI screws in pediatric neuromuscular scoliosis is efficacious with a reasonable safety profile and provides a useful technique for pelvic fixation in children with scoliosis.